Analisis Pelayanan Jamsostek Mobile dalam Meningkatkan Akses dan Kualitas di Karimunjawa Surabaya - Firdiansyah Arief Arianto; Ika Devi Pramudiana; Nihayatus Sholichah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
BPJS Ketenagakerjaan through the Jamsostek Mobile (JMO) application presents digital service innovations to make it easier for participants to access social security programs, especially Old Age Security (JHT) claims. This study aims to analyze JMO services in improving access and quality of services at BPJS Ketenagakerjaan Karimunjawa Surabaya City by using descriptive qualitative methods through interviews, observations, and documentation. The results of the study show that JMO is able to speed up the claims process, increase efficiency, and expand access to information, although obstacles are still found in the form of system disruptions, login failures, document verification, and lack of optimal socialization. Meanwhile, direct service in the office has met quality standards through the provision of representative facilities, professional officers, and inclusive services. The application of the SERVQUAL dimension which includes tangibles, reliability, responsiveness, assurance, and empathy is evident in service practice. Thus, JMO has proven to be effective in supporting the improvement of the quality of BPJS Employment services, although technical improvements, strengthening data verification, and more intensive socialization are still needed so that digital services can be used optimally.